Rancang Bangun Sistem Sortasi Cerdas Berbasis Pengolahan Citra untuk Kopi Beras - Dedy W. Soedibyo; Usman Ahmad; Kudang Boro Seminar; I Dewa Made Subrata (PERTETA, 2010)
Abstrack Coffee has good prospects as a motor of development in Indonesia agribusiness and agroindustry, therefore needs to be handled properly and professionally. Grading process in commercial green coffee asgrain commodity is still done manually. This process has the disadvantage of low efficiency, objectivity and the level of consistency. Therefore weneed a machine that can workautomatically to classify the quality of the green coffee by visual inspection. Theobjective of this study was to design the green coffee sorting machine controlled by a computer based on image processing program consisted of conveyor belt, the image capture station used twodigital cameras, and the parallelsimulator divider. The design of sorting machine was used for the development of the green coffee sorting system that will categorizeinto four quality classes based on the qualifications according to the standard of SCAA ( Specialty Coffee Association of America). Keyword: Sorting Machine, green coffee, image procesing, computer programDiterima: 14 Juli 2010; Disetujui: 11 Oktober 2010